Larangan Menikah di Bulan Suro Perspektif Hukum Adat Jawa dan Hukum Islam (Studi Kasus di Desa Ngampelrejo Kecamatan Bancar Kabupaten Tuban) - Muhammad Hadi Prayitno; Zamroni Ishaq (Universitas Sunan Drajat Lamongan, Indonesia, 2022)
The month of Suro is so important for the Javanese, as well as for the residents of Ngampelrejo village, Bancar Tuban, that they do not dare to have a wedding celebration in that month. There is an assumption that whoever gets married in the month of Suro, his marriage will not last. From this background, the researcher was intrigued. What are the factors that encourage the people of Ngampelrejo village, Bancar sub-district not to marry in the month of Muharram?, (2) What are the views of Islamic law and customary law regarding the prohibition of marriage in the month of Muharram?. To obtain the required data, researchers used several instruments including: interviews, observation, documentation. Interviews were conducted, among others, to those who have carried out this tradition, to religious leaders, community leaders, and members of the Ngampelrejo village community. The conclusions resulting from this study include; first, the habits carried out by their ancestors before and the feeling of being haunted by a sense of worry about something bad that will happen to them if they get married in the month of Suro. Second, in the view of Islamic law, marriages carried out in the month of Suro are considered valid. As for the Javanese tradition in general and in particular the Ngampelrejo community, getting married in the month of Suro is a taboo and as much as possible is not done.